Проблеми систематизації наслідків у специфічних конструкціях складів злочинів - Берзін, П.С. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The article covers the research of the consequences defining criminal-

legal content of element of the corpus delicti. The specific criminal-

legal content of systematization of the consequences in modern criminal

legislation of Ukraine is investigated. Main aspects of the normative

regulation this system of the consequences has been considered. Статья посвящена исследованию последствий, определяющих уголовно-

правовое содержание элемента состава преступления. Исследуется

специфическое уголовно-правовое содержание систематизации последствий по

действующему уголовному законодательству Украины. Рассматриваются

основные аспекты нормативного закрепления такой системы последствий.